2022
DOI: 10.3390/nu14071381
|View full text |Cite|
|
Sign up to set email alerts
|

Usual Nutrient Intake Distribution and Prevalence of Inadequacy among Australian Children 0–24 Months: Findings from the Australian Feeding Infants and Toddlers Study (OzFITS) 2021

Abstract: (1) Background: Breastmilk provides all the nutrition an infant requires between 0–6 months. After that, complementary foods are needed to meet the child’s increasing energy and nutrient requirements. Inadequate energy and nutrient intake may lead to growth faltering, impaired neurodevelopment, and increased disease risk. While the importance of early life nutrition is well recognized, there are few investigations assessing the nutritional adequacy of Australian children <24 months. Here, we describe usual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…As detailed in our previous paper, breastmilk intake may have been underestimated or overestimated as volume assumptions do not account for variation in feeding efficiency between toddlers [ 34 ]. However, the energy intakes for toddlers reported in our study [ 12 ] closely match the estimated energy requirements for this age group [ 7 ]. Maternal age is a strong predictor of continued breastfeeding [ 35 ] and may explain the high breastfeeding rates observed in our sample compared to previous Australian studies.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…As detailed in our previous paper, breastmilk intake may have been underestimated or overestimated as volume assumptions do not account for variation in feeding efficiency between toddlers [ 34 ]. However, the energy intakes for toddlers reported in our study [ 12 ] closely match the estimated energy requirements for this age group [ 7 ]. Maternal age is a strong predictor of continued breastfeeding [ 35 ] and may explain the high breastfeeding rates observed in our sample compared to previous Australian studies.…”
Section: Discussionsupporting
confidence: 79%
“…Although breastmilk has the same amount of energy as toddler or cow’s milk, it contains less than a third of the calcium. Inadequate iron intakes were common in toddlers in our study and around 10% had low calcium intakes [ 12 ]. While the benefits of breastfeeding into the second year is beyond doubt, some toddlers may be receiving too much breastmilk as little practical guidance is given on how and when to offer breastmilk to optimize the consumption of core foods as toddlers transition from a milk-based diet to mostly family foods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FITS studies that have been completed and published are shown in Table 1 [ 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. These studies have been ongoing, and since 2002, there have been seven countries having published results, including the OzFITS studies now published in this Special Issue [ 4 , 5 , 6 , 7 , 8 ]. With each survey this is an opportunity to improve or modify the methodology yet stay consistent with a common analysis approach in more recent FITS such as those in Australia, China, Mexico, the Philippines, Russia, and the United States [ 3 , 4 ].…”
Section: Feeding Infants and Children Studies (Fits)mentioning
confidence: 99%
“…In this Introduction to the Special Issue entitled “Australian Feeding Infant and Toddler Study 2021”, we provide the background to Feeding Infants and Toddlers Studies (FITS) which have, in the past two decades, provided much-needed data on early childhood nutrition that can lead to development of dietary guidelines specific for the first two years of life [ 3 , 4 ]. Appreciating the role FITS can play puts into context the findings of the most recent FITS conducted in Australia, called OzFITS [ 5 , 6 , 7 , 8 , 9 ]. Our purpose is to position OzFITS as a necessary and important step for healthcare professionals in Australia to have for developing dietary guidelines and nutrition education resources for its young children.…”
Section: Introductionmentioning
confidence: 99%